IMU based adaptive blur removal approach using image processing for railway inspection - Santur, Yunus; Karaköse, Mehmet; Aydin, Ilhan; Akin, Erhan (IEEE Computer Society, 2016)
Rail transportation systems, which are commonly used in today's world, should be inspected at certain intervals for possible accidents. During the rail inspection, the physical vibration on rail lines causes a blurring effect on the images. Doing deblurring automatically requires information of blurring rates and specifying the parameters accordingly for deblurring. With this purpose, a test equipment which can move on rail lines and a camera system for the detection of blurring and deblurring is integrated with Inertial Measurement Unit (IMU) is promoted in this study. Then, with Attitude and Heading Reference System (AHRS) algorithm, the effect of blurring at the moment of the vibration is examined, point spread function (PSF) value is chosen dynamically and deblurring is achieved. In order to increase the accuracy rates of detection algorithms, a pre-treatment method is proposed for detecting the blur effect and removing it. © 2016 IEEE.
23rd International Conference on Systems, Signals and Image Processing, IWSSIP 2016 -- 23 May 2016 through 25 May 2016 -- Bratislava -- 122534
Keywords: AHRS; Anomaly Detect; Deblurring; Image Processing; Inertial Measurement Units; Rail Inspection